The relation between Helicobacter pylori and gastroesophageal reflux disease in KSA - Alziyadi, Faisal; Alshammeri, Nouf; Alamer, Ali; Altarouti, Fatimah; Aljehani, Nesreen; Asiri, Khalid; Almarghalani, Fardus; Albalwi, Easa; Almohideb, Malik; hayyan, Ameen (International Journal Of Community Medicine And Public Health, 2018)
Estimates say that Helicobacter pylorus affects more than half of the general population over the world. Its prevalence varies significantly among different areas. Studies done in 1990 reported a prevalence of 70% of people older than 20 years who live in Saudi Arabia, and 40% of people aged 5-10 years. The first line regimen of helicobacter pylori infections in Saudi Arabia is 7 days of triple therapy. However, in areas of high antibiotic resistance, or in cases of failure of triple therapy, a ‘rescue’ quadruple therapy (that contains bismuth) is indicated. In this study we aimed to look at the prevalence of H. pylori infection and its association with gastroesphageal reflux disease in Saudi Arabia. We also tried to understand the approach for diagnoses and treatment in the Kingdom. We did a systematic search for helicobacter pylori and GERD in Saudi Arabia using PubMed search engine (http://www.ncbi.nlm.nih.gov/) and Google Scholar search engine (https://scholar.google.com). The following search terms were used: H. pylori, gastroesophageal reflux disease, prevalence of GERD in Saudi Arabia, lifestyle Saudi Arabia, gastroenterology Saudi Arabia. All studies done shows prevalence in Saudi Arabia to be relatively high (reaching 70%) and increasing. Despite being highly prevalent, no solid guidelines are present to help clinicians diagnose and treat helicobacter pylori infection properly. These, along with other causes like improper use of antibiotics have led to the emerging of new strains that are resistant to typical antibiotic treatment.